BATAS USIA KAWIN MENURUT UU. NO 1 TAHUN 1974 DALAM KAITANNYA DENGAN KEBIJAKAN KEPENDUDUKAN - Ahmad Basuki (Perspektif, 2002)
One aspect of birth control in demography dynamics is a restraint of marital age. As mentioned in UU No. 1/1974, normatively, marital age of male is 19 years old, while female is 16. However, empiric study indicated that indonesian culture (i.e. to have their children get married at a very early age) is a major factor in discourage the implementation of the regulations. Further study and action must be taken to overcome this reality due to the achievement of national policy in demography.